All Days 2007
DOI: 10.4043/18700-ms
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Seismic Velocity Sensitivity To Production-Induced Strain at the Ekofisk Field

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractIn chalk reservoirs such as the Ekofisk Field, fluid flow and geomechanical effects combine to change both the location and properties of the reservoir and overburden. Pore pressure and fluid saturation changes cause reservoir compaction and perturb the elastic properties of the reservoir rocks. The overburden responds to the compaction with piston-like seafloor subsidence and length changes (strains). These overburden strains change the seismic velocity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The exception to this is a synthetic sandstone, for which R is measured under unloading as 75, whilst loading gives 15, but unloading after loading is 55. Similarly, Janssen et al (2007) observed values of 10-30 for Ekofisk chalk in the laboratory (as opposed to 2-6 in the 4D seismic data). Bathija, Batzle and Prasad (2009) measured three sandstones and one shale sample under hydrostatic and uniaxial loading, and found Rfactors of between 6 and 91 for the sandstones and 6-11 for the shales.…”
Section: Seismic Data Analysis and The Empirical R-factormentioning
confidence: 56%
See 4 more Smart Citations
“…The exception to this is a synthetic sandstone, for which R is measured under unloading as 75, whilst loading gives 15, but unloading after loading is 55. Similarly, Janssen et al (2007) observed values of 10-30 for Ekofisk chalk in the laboratory (as opposed to 2-6 in the 4D seismic data). Bathija, Batzle and Prasad (2009) measured three sandstones and one shale sample under hydrostatic and uniaxial loading, and found Rfactors of between 6 and 91 for the sandstones and 6-11 for the shales.…”
Section: Seismic Data Analysis and The Empirical R-factormentioning
confidence: 56%
“…Similarly, Janssen et al . () observed values of 10–30 for Ekofisk chalk in the laboratory (as opposed to 2–6 in the 4D seismic data). Bathija, Batzle and Prasad () measured three sandstones and one shale sample under hydrostatic and uniaxial loading, and found R‐ factors of between 6 and 91 for the sandstones and 6–11 for the shales.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations